Analisis Perbandingan Pengendalian Persediaan Bahan Baku Tempe Keripik Menggunakan Metode EOQ Dan POQ - Resa Aulia Febriansyah; Widya Setiafindari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted to help Sudarmi Tempe Chips MSMEs to compare between the Economic Order Quantity and Periodic Order Quantity methods which is more efficient. In addition, it also knows how much Safety Stock of tempeh raw materials is available to Sudarmi Crispy Tempeh MSMEs. from controlling raw materials using the Economic Order Quantity method and the Periodic Order Quantity method is a more efficient procurement of raw materials, with 9 times more order frequency., the number of orders is 1,944 pcs tempeh, and the total cost is Rp 583,768. For the safety stock of raw materials, the supply of tempeh raw materials is 139 pcs.